PREVALENCE OF HYPERTENSION AMONG OBESE AND NON-OBESE PATIENTS WITH CORONARY ARTERY DISEASE - Khan, Sher Bahadar; Noor, Lubna; Rehman, Hafiz -ur-; ullah, Hameed; Hafeezullah, Mohammad; Awan, Zahid Aslam; Din, Shahab ud; Shah, Syed Sadiq (Journal of Ayub Medical College Abbottabad, 2010)
Background: Globally, obesity is now recognised as an epidemic. The degree of obesity is proportional to the rate of development of cardiovascular diseases, hence, resulting in a dramatic increase in morbidity and mortality. Apart from obesity, hypertension is another well recognised risk factor contributing to coronary artery disease (CAD). The precise prevalence of obesity-related hypertension varies with age, race and gender; and is yet unknown in our population. The objective of this study was to determine the prevalence of hypertension in obese and non-obese patients with diagnosed CAD. Methods: This hospital based descriptive study was conducted in Cardiology Department of Postgraduate Medical Institute, Lady Reading Hospital, Peshawar from 15th March 2007 to 30th May 2008. A total of 200 patients with diagnosed CAD were enrolled, 100 were found obese and 100 non-obese. Results: Among these, a total of 111 (55.5%) were found to be hypertensive, 66 (59.46%) of these were obese and 45 (40.54%) non-obese (p=0.003). Conclusion: Obese patients with CAD had significantly more frequent hypertension. Keywords: Coronary Artery Disease, CAD, Body Mass Index, BMI, Obesity, Hypertension